Identifying undamaged-beam status based on singular spectrum analysis and wavelet neural networks - Nguyen, Dung Sy; Nguyen, Hung Quoc; Ngo, Nhi Kieu (Journal of Computer Science and Cybernetics, 2016)
In this paper, the identifying undamaged-beam status  based on singular spectrum analysis (SSA) and wavelet neural networks (WNN)  is presented. First, a database is built from measured sets and SSA which  works as a frequency-based filter. A WNN model is then designed which consists of the wavelet frame building, wavelet structure designing and  establishing a solution for training the WNN. Surveys via an experimental  apparatus for estimating the method are carried out. In this work, a  beam-typed iron frame, Micro-Electro-Mechanical (MEM) sensors and a  vibration-signal processing and measuring system named LAM_BRIDGE are all  used.